2014
DOI: 10.2527/jas.2013-6776
|View full text |Cite
|
Sign up to set email alerts
|

Space allowance and high fiber diet impact performance and behavior of group-kept gestating sows1

Abstract: Identifying and optimizing housing and management systems that improve the well-being of the gestating sow is essential to sustaining animal agriculture. Therefore, the impact of 2 floor-space allowances and a high-fiber gestation diet on dry group-housed sows were evaluated using multiple measures of well-being. Groups of 10 multiparous sows/pen (n = 221) were assigned randomly to treatments in a 2 × 2 factorial arrangement to either a corn-soybean meal diet (CTL) or corn-soybean meal diet supplemented with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Although individual rationing is more easily achieved when dry sows are individually housed in stalls compared to grouped in pens (Johnston and Li, 2013;Young et al, 2004), there is impetus for the industry to change from individual stalls to group housing. In advance of the change, research is occurring on group housing of dry sows, including sow feeding strategies (e.g., Schneider et al, 2007;DeDecker et al, 2014) and the potential impacts of group housing on sow welfare and production (e.g., Salak-Johnson et al, 2007; Gonyou et al, 2013;Hemsworth et al, 2013. Whereas Gonyou et al (2013) emphasized the importance of establishing sow groups based on nutritional requirements, the delivery of feed to the animal and the mean consumption rate was 1,859.8 g/min for the first 5 min and 1,060.7 g/min for the first 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…Although individual rationing is more easily achieved when dry sows are individually housed in stalls compared to grouped in pens (Johnston and Li, 2013;Young et al, 2004), there is impetus for the industry to change from individual stalls to group housing. In advance of the change, research is occurring on group housing of dry sows, including sow feeding strategies (e.g., Schneider et al, 2007;DeDecker et al, 2014) and the potential impacts of group housing on sow welfare and production (e.g., Salak-Johnson et al, 2007; Gonyou et al, 2013;Hemsworth et al, 2013. Whereas Gonyou et al (2013) emphasized the importance of establishing sow groups based on nutritional requirements, the delivery of feed to the animal and the mean consumption rate was 1,859.8 g/min for the first 5 min and 1,060.7 g/min for the first 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] In an attempt to limit these behaviors, researchers have fed sows high-fiber gestational diets which are bulkier and increase feeding duration and improves satiety 46,47 and these diets have also been shown to reduce sham-chewing, bar biting, and foraging-like behaviors in sows. 32,42,46 Moreover, feeding fiber to group-housed sows increased time spent lying and decreased aggressive behavior. de Leeuw 48 found that sows fed a high-fiber diet spent less time active and made less frequent postural changes for several hours post-feeding and others reported not only a decrease in general activity but an increase in time spent lying.…”
Section: Managing Aggression Group-housing Feeding Strategiesmentioning
confidence: 97%
“…Also, total lesion severity scores were higher for sows kept at 1.7m² as opposed to 2.3m² of floor-space per sow. 32 Anil 33 found that sows managed dynamically in pens with an electronic sow feeding system had higher injury scores compared to sows maintained in static groups or only mixed twice. Similarly, sows managed in a static group of 35-40 sows per group had less lesions than if sows were managed in a dynamic group with more than 100 sows per pen.…”
Section: Other Housing Components Impact Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy was confirmed at day 27±2 post-mating using ultrasound machine (Bantam, IE Medical Imaging) for transabdominal examinations. Sows were individually fed at 0800 h a fiber modified diet mainly of shelled corn and soybean meal with a portion of these ingredients being replaced with wheat middlings (15%) and soybean hulls (30%) as described in DeDecker et al (2014). All nutrients were present at concentrations that met or exceeded nutrient requirements (NRC, 1998).…”
Section: Animals and Housingmentioning
confidence: 99%